Amazing Escapes: Illustrated with Photographs and Prints - Gunning, Thomas G. (Dodd, Mead, 1984)
Presents nine tales of escape and survival against great odds including escapes from a great white shark, a volcanic eruption, and a fall through a thunderstorm.
Keywords: Escapes; Juvenile literature; Juvenile literature; Adventure and adventurers; Juvenile literature; Survival; dept.rdg; faculty_collection